2008
DOI: 10.1007/s00192-008-0562-6
|View full text |Cite
|
Sign up to set email alerts
|

Determining the shape of the turns–amplitude cloud during anal sphincter quantitative EMG

Abstract: We aimed to compare our normative data for quantitative interference pattern (IP) analysis of the anal sphincter to previously published data. In 28 nulliparous women, we performed IP analysis during quantitative concentric needle electromyography (QEMG) of the anal sphincter. At each sampling site, a 500-ms epoch was analyzed. The data were log transformed. Linear regression lines (with 95% confidence intervals) were calculated from the log transformed variables "turnssecond" and "amplitude-turn." These confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Other investigators have reported similar findings in the EAS [26, 27], suggesting that MUP changes associated with reinnervation may be more prominent in MUP activated at higher levels of muscle force generation. Therefore, IP analysis may be a better method to detect small changes in MUP parameters.…”
Section: Discussionsupporting
confidence: 66%
“…Other investigators have reported similar findings in the EAS [26, 27], suggesting that MUP changes associated with reinnervation may be more prominent in MUP activated at higher levels of muscle force generation. Therefore, IP analysis may be a better method to detect small changes in MUP parameters.…”
Section: Discussionsupporting
confidence: 66%
“…Re-innervation changes may be more prominent in MUP activated at higher levels of muscle force generation; therefore, by analyzing different MUP, the techniques together may offer additive insight into neuromuscular function. Other investigators have reported similar findings in the external anal sphincter (21, 22) suggesting that MUP changes associated with reinnervation may be more prominent in MUP activated at higher levels of muscle force generation. Therefore, IP analysis may be a better method to detect small changes in MUP parameters.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, multi‐MUP analysis has several advantages: automatization of MUP extraction enabling rapid sampling of a large number of MUPs in a short time; simultaneous sampling of many MUPs at 1 investigation site; lower bias in MUP selection; and the possibility to manually discard MUPs containing too many artifacts . As previously reported, IP analysis is a practical technique to study the neuromuscular function of the striated muscles of the pelvic floor . The well‐established technique of “cloud analysis” can be used to evaluate muscle interference patterns, independently from the force of contraction …”
Section: Discussionmentioning
confidence: 99%
“…For IP analysis, several 500 ms‐epochs of EMG signal (IP samples) were recorded automatically from different sites in both parts of the EUS, at different levels of voluntary and reflex muscle activation. Only samples with a sufficiently crisp EMG signal were included in the analysis, corresponding to positive values for all IP parameters. Furthermore, patients with less than 15 samples were excluded.…”
Section: Methodsmentioning
confidence: 99%